Enhancement of intestinal mucosal immunity and immune response to the foot-and-mouth disease vaccine by oral administration of danggui buxue decoction - Zhou, Bingxin; Huang, Huan; Gui, Fuxing; Bi, Shicheng; Du, Hongxu; Cao, Liting (Frontiers in Veterinary Science, 2022)
This study investigated the effect of Danggui Buxue decoction (DBD) on the immunity of an O-type foot-and-mouth disease (FMD) vaccine and intestinal mucosal immunity. SPF KM mice were continuously and orally administered DBD for 5 d and then inoculated with an O-type FMD vaccine. The contents of a specific IgG antibody and its isotypes IgG1, IgG2a, IgG2b, and IgG3 in serum and SIgA in duodenal mucosa were determined by ELISA at 1 and 3 W after the 2nd immunization. qRT-PCR was used to detect mRNA expression levels of IL-4, IL-10, IFN-γ, and IL-33 in the spleen, and mRNA expression levels of J-chain, pIgR, BAFF, APRIL, IL-10, IFN-γ and IL-33 in the duodenum. The results showed that compared with the control group, oral administration of DBD significantly increased levels of the anti-FMD virus (FMDV)-specific antibodies IgG, IgG1, and IgG2a in the serum of O-type FMD vaccine-immunized mice 1 W after the 2nd immunization (P < 0.05), upregulated mRNA expression levels of spleen lymphocyte cytokines IL-4 and IL-33 (P < 0.05), promoted the secretion of SIgA in duodenal mucosa (P < 0.05). The mRNA expression levels of J-chain, pIgR, BAFF, APRIL, IL-10, and IL-33 in duodenal tissues were upregulated (P < 0.05). This study indicates that DBD has a good promotion effect on the O-type FMD vaccine and the potential to be an oral immune booster.